Android Quran Applications: Revolutionizing Learning and Teaching - Lubna Iftikhar; Dr. Amir Hayat; Sadia (Al Manhal Research Journal, 2024)
Android Quran applications are mobile programs planned for Android gadgets that help people and communities learn and educate themselves about the Holy Quran. These applications have picked up gigantic popularity and have become a fundamental apparatus for day-to-day life direction for millions of Muslims around the world. People may study, consider, and determine with the lessons of the Quran on a straightforward and readily accessible stage through Quran applications. These applications give an in-depth understanding of the Quran at believers' fingertips, with highlights counting the full content of the Quran, interpretations, recitations, tafsir (exposition), and search capabilities. By recognizing both the opportunities and challenges, this article points to a comprehensive overview of the role Android Quran applications play in shaping the future of Quranic learning. It will provide the opportunity for more research and discussion on the most effective strategies to utilize innovation to improve our understanding and learning of the Sacred Quran.